Bionic microstructure on titanium alloy blade with belt grinding and its drag reduction performance. (December 2021) - Xiao, Guijian; He, Yi; Huang, Yun; He, Shui; Wang, Wenxi; Wu, Yuan
Researches show that surface with bionic structure plays an important role in improving the aerodynamic performance on aero engine parts. Belt grinding, a popular method to process titanium alloy parts such as aero-engine blade, is also found that it can be used to obtain bionic microstructure through special grinding method and parameters. In order to explore the performance of bionic microstructure processed by belt grinding and its effects on airflow dynamics, several groups of simulation and an experiment are carried out in this paper. Firstly, the mechanism of drag reduction of bionic microstructure is discussed. It shows that the effect of drag reduction of bionic microstructure is related to protrusion height, which is related to the shape and size of the bionic microstructure. Then, three groups of typical belt grinding bionic microstructure are set up. In addition, the drag reduction values are calculated in CFD simulation. The results are analyzed and discussed. Further, to verify the airflow dynamics of drag reduction of belt grinding bionic microstructure, an experiment of aero-engine blade is carried out. Finally, the effects of airflow dynamic performance of blade with belt grinding bionic microstructure are obtained in CFD simulation. In general, the shape of wave ribs, compared to V-ribs and trapezoidal ribs, has the best performance in drag reduction. To a certain extent, the improvement of airflow dynamic performance is higher with the increasing of the size of bionic microstructure, which suggests lower feed rate and higher grinding pressure for bionic structure.